Experiences and Support Needs of Caregivers of Patients with Higher-Risk Myelodysplastic Syndrome via Online Bulletin Board in the USA, Canada and UK - Pauline Frank; Anne Olshan; Tracey Iraca; Cindy Anthony; Sophie Wintrich; Emma Sasse (Oncology and Therapy, 2023)
Abstract Introduction Patients with higher-risk myelodysplastic syndromes (MDS) face considerable challenges in disease management and often require caregiver support. Reports on the burden of caring for patients with advanced cancer suggest that caregivers receive insufficient support. Our research aimed to identify key challenges for caregivers of patients with higher-risk MDS. Methods Online bulletin board is a qualitative research methodology which enables data collection via a web-based platform. A mix of moderator-led discussion guide and interparticipant discussion provides the caregiver insights as online dialogue, which then undergo content analysis to extract key findings. Results Sixteen caregivers participated from the USA (n = 5), UK (n = 6) and Canada (n = 5). Content analysis identified the caregiver experience in higher-risk MDS as multifactorial, with seven key categories of caregiver burden: caregiver role and burden, mental health, family dynamics, disease experience, treatment experience, healthcare professional (HCP) interactions and information and education. Conclusion There is significant impact and burden on caregivers of patients with higher-risk MDS, which varies depending on disease stage, choice (or lack of choice) of treatments, and the personal situation of the caregiver. Emotional stress occurs mostly at diagnosis/prognosis stage and when told to ‘watch and wait’, which is amplified when HCPs are perceived to lack knowledge/expertise about MDS. There is a need for better education about MDS for HCPs, patients, caregivers and the general community; a need for improved communication between patients/caregivers and HCPs; and a high unmet need for better mental health and emotional support for both patient and caregiver.